Consumer Protection in the Use of Traveloka Paylater - Litaay, Elsina Agustina Minely Litaay; Tjoanda, Merry; Kuahaty, Sarah Selfina (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: In the current era of economic globalization, the growth of the business world requires balanced support between consumer protection and business actors, especially in the context of technology that is increasingly developing, one of which is financial technology.Purposes of the Research: The research aims to analyze and discuss the legal protection that consumers get in the use of Traveloka Paylater as well as to examine and analyze the liability of Traveloka Paylater if consumers are harmed in the use of paylater.Methods of the Research: The research method used is with the type of normative legal research and the research approach of legal concept analysis with the Library Research collection technique.Results Main Findings of the Research: The findings of the study show that the Form of Legal Protection for consumers who use traveloka paylater is carried out through the provision of Information and Consumer Protection through the provision of Clear and Comprehensive Terms and Conditions, making a Refund and Transaction Cancellation Policy as a Form of Consumer Protection in the face of unwanted or problematic situations, a Fair and Transparent Dispute Resolution Mechanism is a means of legal protection that important to consumers. Traveloka's liability if consumers are harmed in the use of paylater is strict liability. Traveloka in this case has an obligation to be responsible through compensation to consumers This refers to the principle of absolute liability (Strict Liability), which no longer questions about whether or not there is a fault, but business actors are directly responsible for the losses experienced by consumers.